Impact of Black Garlic extract on cardio-renal protection in hypertensive animal models - Hasimun, Patonah; Putra, Hendra Mahakam; Choerunnisa , Fitriani (Universitas Ahmad Dahlan, 2025)
A strong link exists between arterial stiffening and cardiovascular conditions, particularly hypertension. Hypertension, a significant contributor to mortality rates, particularly affects elderly populations. The processed form of Allium sativum, known as black garlic, is renowned for its medicinal properties, including its ability to lower blood pressure. This study examined the blood pressure-lowering effects of black garlic extract, employing male Wistar rats aged two to three months.The experiment involved six distinct rat groups, each comprising of four animals. The two groups served as controls, whereas the remaining four underwent different treatments. Captopril was administered to one group at a dose of 2.5 mg/kg, whilst the remaining three groups were given black garlic extract as BG50, BG100, and BG200. All groups, with the exception of the control normal, underwent a 28-day induction protocol that included 25% fructose in drinking water, cholesterol (200 mg/kg), and propylthiouracil (12.5 mg/kg). The test substances were administered starting on day 14 concurrently with the induction phase. The evaluated parameters included blood pressure, arterial stiffness, nitric oxide (NO) levels, and renal histopathology. Black garlic extract significantly lowered blood pressure, enhanced arterial elasticity, and increased NO levels (p < 0.05) compared with the controls. Renal histopathological analysis revealed protective effects, suggesting prevention of kidney damage. These findings suggest that black garlic may have cardiorenal protective effects and could be useful for managing hypertension and arterial stiffness.